Inventing the Grand Banks: A Deep Chart. Humanities GIS, Cartesian, and Literary Perceptions of the North-West Atlantic Fishery ca 1500-1800 - Holm, Poul; Travis, Charles; Ludlow, Francis; MATTHEWS, JOHN ALPHONSUS; HAYES, PATRICK; Rankin, Kieran; Legg, Robert; Nicholls, John; Lougheed, Kevin; Allaire, Bernard; Towns, Lydia (My University, 2020)
As a feature of the Fish Revolution (1400–1700), the early modern “invention” of the Grand Banks in literary and cartographical documents facilitated a massive and unprecedented extraction of cod from the waters of the north Atlantic and created the Cod/Sack trade Triangle. This overlapped with the southern Atlantic Slave, Sugar, and Tobacco Triangle to capitalise modern European and North American societies. In 1719, Pierre de Charlevoix claimed that the Grand Banks was “properly a mountain, hid under water,” and noted its cod population “seems to equal that of the grains of sand which cover this bank.” However, two centuries later in 1992, in the face of the collapse of the fishery, and fearing its extinction, a moratorium was placed on five centuries of harvesting Grand Banks cod. The invention and mining of its waters serves as a bellwether for the massive resource extractions of modernity that drive the current leviathan and “wicked problem” of global warming. The digital environmental humanities narrative of this study is parsed together from 83 pieces of Grand Banks charting from 1504 to 1833, which are juxtaposed through Humanities GIS applications with English and French cod‐catch records kept between 1675 and 1831, letters regarding Cabot's 1497 voyage, Shakespeare's The Tempest (1611) and scientific essays by De Brahms (1772) and Franklin (1786).
Keywords: GIS; Fisheries; Cartography; Geographical history; Literary geography; Digital Humanities; Smart & Sustainable Planet; Environmental Humanities; History